Respuesta :
Answer: The correct option is
(C) (3, 4).
Step-by-step explanation: We are given to find the solution (a, c) to the following system of linear equations :
[tex]2a-3c=-6~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\a+2c=11~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)[/tex]
Multiplying equation (ii) by 2, we have
[tex]2(a+2c)=2\times11\\\\\Rightarrow 2a+4c=22~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(iii)[/tex]
Subtracting equation (i) from (iii), we get
[tex](2a+4c)-(2a-3c)=22-(-6)\\\\\Rightarrow 7c=28\\\\\Rightarrow c=\dfrac{28}{7}\\\\\Rightarrow c=4.[/tex]
From equation (i), we get
[tex]2a-3\times4=-6\\\\\Rightarrow 2a=12-6\\\\\Rightarrow 2a=6\\\\\Rightarrow a=\dfrac{6}{2}\\\\\Rightarrow a=3.[/tex]
Thus, the required solution is (a, c) = (3, 4).
Option (C) is CORRECT.
The solution (a, c) to this system of linear equations is (3, 4)
System of equations
Given the system of equations expressed as:
2a – 3c = –6
a + 2c = 11
From equation 2; a = 11 - 2c
Substitute into equation 1 to have:
2(11-2c) - 3c = -6
22 - 4c - 3c = -6
22 - 7c = -6
-7c= -28
c = 4
Recall that a = 11 - 2c
a = 11 - 2(4)
a = 11 - 8
a = 3
Hence the solution (a, c) to this system of linear equations is (3, 4)
Learn more on system of equation here: https://brainly.com/question/14323743